(untitled) - Farlow, Stanley J. (New York, 1994)
This text is intended for a one-term course in introductory differential equations and is designed for students in pure and applied mathematics who have had a course in calculus. The text strives to present a balance of mathematical rigor and intuitive thinking; and ideas and concepts are developed thoroughly in a clear and informal style. An extensive illustration program enhances the conceptual material and allows the students to visualize the mathematics. An optional treatment of chaotic dynamical systems introduces the student to the basic ideas surrounding chaotic motion. Special features include excellent problem sets which contain computer applications, brief historical notes, and exercises that require the student to learn through writing.
Keywords: Differential equations